Seekers and Seers: Lay Buddhists and Buddhist Revival in Rural China = fu tou yu shen po: nong cun de ju shi fu jiao yu zhong guo dang dai fu jiao fu xing - Chao, Shin-yi (Review of Religion and Chinese Society, 2022)
This paper explores lay Buddhism in contemporary rural North China through investigating the practice and practitioners of "Buddha-chanting" (nianfo 念佛) in relation to local religion, monastic Buddhism, and spirit mediums. The nianfo groups are led by and consist of ordinary villagers, overwhelmingly female. They meet in private houses or village temples of local deities. The groups are not subject to the authority of clergy, but individual group members, especially the leaders, may maintain a close relationship with a Buddhist monastery. These individuals are a link from monastic Buddhism to the Buddhist masses in villages, and the nianfo groups are the nexus of the networks. Members of the nianfo groups have a clear sense of being Buddhist while they also participate in activities of local religion. In addition, village spirit mediums, with whom the villagers often consult during crises, command some influence. They have also played a consequential role in the process of restoring Buddhism in the area.